Pengaruh Hedonic Shopping Value, Shopping Lifestyle, dan Gamification terhadap Impulse Buying pada Generasi Z Pengguna Tiktok Shop di Kota Kabanjahe - Afrida, Desri; Darmansyah, Muthya Rahmi; Amelia, Wan Rizca; Tobing, Fitriani (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to determine: The Influence of Hedonic Shopping Value, Shopping Lifestyle, and Gamification on Impulse Buying in Generation Z TikTok Shop Users in Kabanjahe City. The research method used in this study is quantitative. By distributing questionnaires to 390 generation Z respondents in Kabanjahe City. The data analysis technique uses multiple linear regression. With the results of the study. (X1) Hedonic Shopping Value, has a significant effect on Impulse Buying. This can be seen from the significant value (0.001) <0.10 and t-count (3.497)> compared to t-table (1.649). (X2) Shopping Lifestyle has a significant effect on Impulse Buying. This can be seen from the significant value (0.000) <0.10 and t-count (10.018)> compared to t-table (1.649). (X3) Gamification does not have a significant effect on Impulse Buying. This can be seen from the significant value (0.808) > 0.10 and the t-count (0.243) < compared to the t-table (1.649) (4) that (Hedonic Shopping Value, Shopping Lifestyle, and Gamification) simultaneously are significant towards Impulse Buying, as can be seen from the F-count > F-table and the level of significance (0.000) < 0.10